Comparison of the Z/gamma* + jets to gamma + jets cross sections in pp collisions at root s = 8 (vol 10, 128, 2015) - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (My University, 2016)
An error was found in the published version in the top right plots in figure 2 and figure 3. In both cases the normalization of the photon plots is incorrect by the factor of the luminosity of 19.7. The corrected figures are shown below. The physics conclusion of the paper remains unchanged, since the ratio plots are unaffected.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2016). Comparison of the Z/gamma* + jets to gamma + jets cross sections in pp collisions at root s = 8 (vol 10, 128, 2015). Journal of High Energy Physics(4), 21. doi:10.1007/jhep04(2016)010
Keywords: Physics